Seeing the point from which you see what you see: An essay on epistemic reflexivity in language research - Salo, Linus (Multilingual Margins: A journal of multilingualism from the periphery, 2018)
This essay deals with epistemic issues in language research, focusing particularly on the field of language planning and policy (LPP). It outlines Pierre Bourdieu’s principle of epistemic reflexivity as a device for understanding what the view of the research object owes to the researcher’s past and present position in social space. I hold that developing such an understanding is particularly vital for LPP scholars, by virtue of the ways in which the objects investigated here tend to linger in the borderlands between science and politics. Accordingly, the essay unearths the philosophical roots of epistemic reflexivity and highlights some of its implications in the research practice with examples from Swedish LPP research. It also examines the value of a reflexive stance in interviews as a way of pinpointing the relevance of epistemic reflexivity in every moment of the scholarly investigation. In conclusion, the argument is that since epistemic reflexivity is a useful device for any critical researcher who wishes to grasp the knowledge he or she produces, it is so also for language researchers, and particularly so in relation to the ideologically normative practices of LPP scholarship. Therefore, a reflexive gaze is a pivotal driver for yielding better language research.